A Survey on Cross Layer Design based Routing Protocols in Manets - Gayatri, V.; M.Senthil Kumaran, Dr. (International Journal of Engineering and Technology, 2018)
MobileÂ AdHocÂ Network which is abbreviated as MANETÂ is usuallyÂ outlinedÂ as a system or network that hasÂ severalÂ free or autonomous nodes,Â typicallyÂ composed of mobile devices orÂ alternative mobileÂ items,Â which willÂ prepareÂ themselves inÂ variedÂ ways in whichÂ and operateÂ while notÂ strictÂ top-downÂ network administration. Rising attention and permit interested in technology of wireless networking is emphasizing novel experiments in developing optimized communication protocols. Conventionally, architecture of protocols has severe layering principles,Â which assures ability, rapidÂ organizing, andÂ cost-effectiveÂ applications. Still, absence of direction among layers bounds the act of such architectures due to the precise experiments postured by communication links of wireless environment. Cross layer method is developed to overcome such drawbacks. The main idea of cross layer method is to allow coordination, interaction among different layers. This paper presents different cross layer plan models, different cross layer based steering conventions created by different researchers in MANETs, and different issues which are under dynamic research.Â Â